Implikasi Hukum Kesenjangan Regulasi dalam Pencatatan Identitas Ayah - Hakim, Zainul; Dahlan, Moh.; Ishaq; Huda, Mokhammad Miftakhul; Aftab Haider, Aftab Haider (Jurnal Hukum Islam, 2025)
The child lineage under Islamic law and its implementation in Indonesia’s civil registration system face complex challenges that impact the protection of children’s rights. This study examines lineage under Islamic law and its implications for the registration of biological fathers, particularly for children born out of wedlock. This study adopts empirical juridical methods with qualitative, statutes, and conceptual approaches. Although the Constitutional Court ruling has opened the way for the civil recognition of biological fathers, its implementation conflicts with the principle of lineage under Islamic law, which limits inheritance and maintenance rights. Regulatory gaps in civil registration create legal uncertainty and are potentially discriminatory against children’s civil rights. The author argues that policy harmonization that balances the protection of children’s civil rights with respect for Islamic legal values, increases the socialization of legal procedures, and strengthens child protection mechanisms is key to addressing this issue. These findings underscore the need for a balanced approach that combines Islamic legal principles with administrative requirements to protect children’s rights.